The (in)trascendence of love: an analysis of the teleserie What a sad life - Acevedo Zárate, Álvaro Domingo (2019)
This research aims to inquire about the role attributed to love in the construction of the identity of a cynical subject through the analysis of dialogue and body language. For this, the Spanish series What a sad life is analyzed, an audiovisual production that was transmitted, first, by the YouTube video platform and then by television between 2005 and 2010. This series is analyzed in the light of the philosophical approaches of Peter Sloterdijk, Alain Badiou and Slavoj Žižek, as well as the psychoanalytic theory of Jacques Lacan. The conclusions that are reached show us that the series states that the cynical subject, to be one, must give up a «real» encounter with the other, since he lives in self-absorption in search of his own enjoyment and he sees other people as mere instruments. However, the series also states that there is a way to break the isolation of the cynical subject: love. But a love lived as what the French philosopher Alain Badiou calls «a process of truth», because if it is lived differently, love loses all its liberating power and becomes a mere simulation that only reaffirms the subject in his cynicism and, therefore, in his isolation.